The Indigenous Land Struggles Amidst the Pressures for Change in the Lake Toba Areas of North Sumatra, Indonesia - Betty B. S. Naibaho; Shew-Jiuan Su (Forest and Society, 2025)
Many Masyarakat Adat (Indigenous People), including those in the Lake Toba areas of North Sumatra, Indonesia, struggle to protect their rights to land and resources. This article examines the agencies and dynamics of indigenous-land-related development in Lake Toba amidst modernization, focusing on their roles, relationships, perceptions, interests, and strategies. Semi-structured interviews using snowball sampling were conducted with Indigenous People around Lake Toba, local NGOs, and local government representatives. Five key groups were identified in the process of procuring Indigenous land use rights for the Toba Batak ethnic group: tribal leaders (elders), community members, land dealers, local government, and NGOs. The study found that the Indigenous People’s movement faces challenges beyond political economic structural vulnerabilities, which include economic pragmatism, diminishing cultural values, and rising individualism among community members. The study advocates for political empowerment through multiple strategies that enhance knowledge of the environment and cultural heritage. Legal reforms focused on Indigenous People’s rights and economic empowerment are fundamental in this light. While individual land registration should continue, communal land recognition and protection can also be supported through legal reforms for customary land ownership.